View of Tufts campus and construction of Barnum Hall (Tufts Archival Research Center, 2014)
This date is approximate. photographic prints. Buildings visible in the photograph are West Hall, Goddard Gymnasium, Barnum Hall (under construction), East Hall, and Goddard Chapel.